1997
DOI: 10.1002/jor.1100150121
|View full text |Cite
|
Sign up to set email alerts
|

Tissue characterization of symptomatic and asymptomatic disc herniations by quantitative magnetic resonance imaging

Abstract: The purpose of this investigation was to determine differences in tissue composition of symptomatic and asymptomatic disc herniations as reflected in T1 and T2 relaxation times (quantitative magnetic resonance imaging). Thirty patients with sciatica severe enough to require a discectomy and 46 asymptomatic volunteers (controls) were included in this study. Both groups had a clinical examination as well as a magnetic resonance investigation of the lumbar spine. The longitudinal and transverse magnetic relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…7) (R ¼ À0.51, p < 0.001) (34). From these data, it can be seen that compared with T 2 values in normal discs of $65 ms (29), T 1r at 1.5 T is longer than 100 ms (34). There are no data on field strength dependence and frequency dispersion for T 1r in intervertebral disc in the literature, but this work is clearly warranted.…”
Section: Mri Relaxation Time Measurementsmentioning
confidence: 81%
“…7) (R ¼ À0.51, p < 0.001) (34). From these data, it can be seen that compared with T 2 values in normal discs of $65 ms (29), T 1r at 1.5 T is longer than 100 ms (34). There are no data on field strength dependence and frequency dispersion for T 1r in intervertebral disc in the literature, but this work is clearly warranted.…”
Section: Mri Relaxation Time Measurementsmentioning
confidence: 81%
“…Disc protrusions are not uncommon in asymptomatic adult populations, with prevalences ranging from 10% to 30%, depending on the studied age group. [12][13][14][15][16][17][18][19][20] In general, epidemiologic studies demonstrate that the prevalence of disc protrusions in asymptomatic populations increases with age. [12][13][14][15][16][17][18][19][20] Our study found that nearly 20% of asymptomatic patients 50 years of age or younger had disc protrusion compared with nearly 40% in the symptomatic group.…”
Section: Discussionmentioning
confidence: 99%
“…One report suggested that T2 relaxation times were lower in the lumbar disks that investigators determined were symptomatic disks than in the ones that they determined were not. 3 …”
Section: Discussionmentioning
confidence: 99%
“…T2 relaxation times have been used experimentally to measure disk aging and degeneration. [1][2][3][4] To validate its use, T2 relaxation times in cadaver disks have been correlated with the disk morphology or biochemistry. [5][6][7][8][9][10] The purpose of this study was to test the hypothesis that T2 relaxation time decreases as the stage of lumbar intervertebral disk degeneration advances.…”
mentioning
confidence: 99%